English Medium Instruction (EMI) in a Spanish University - Sonja Andjelkov (CLIL Journal of innovation and research in plurilingual and pluricultural education, 2022)
This article reports on the case of a non-native English-speaking university instructor who teaches her academic subject in the English Medium of Instruction (EMI) track of the Primary Teacher-Education Bachelor’s Degree programme offered by a publicly- funded Catalan university. By means of three semi-structured interviews with the instructor, this study seeks to explore whether and how content and language are integrated into her EMI teaching and assessment practices. Analysis of the instructor’s comments suggests that, on a practical level, the change in the language of instruction seems to change the dynamics of how she teaches and consequently how she assesses, leading to points of conflict among her rationale, institutional policy, and her students’ needs. This tension is most sharply felt when the instructor tries to cope with the lack of clear assessment criteria that could be applied fairly and consistently. The study concludes by noting the practical implications of these results for pre-service teacher education.